Civil-Military Cooperation in Strengthening the National Air Security System - Koloay, Jorry Soleman; Gafur, Hanief Saha (Budapest International Research and Critics University, 2021)
Weak coordination and communication, the existence of sectoral egos between agencies and the tendency to act independently without acting together have resulted incohesiveness and speed of response handling the state against various threats and violations of airspace becomes weak which ultimately affects the condition of national security. The concept of civil-military cooperation to strengthen the national airspace security system is developed through the formulation of the National Airspace Management Bill, the establishment of institutions that facilitate coordination and cooperation between civil-military agencies and the appointment of a command and control center for operations that integrates and harmonizes the operations of all agencies. This study uses a qualitative approach with a qualitative narrative analysis method, to discuss theories, review policies and analyze expert opinions on the need for civil-military cooperation to strengthen the national airspace security system, to then draw conclusions and recommendations.